Family with Sequence Similarity 213, Member A is Associated with the Fertility Selection Index in Holsteins - Mayumi, Sugimoto; Yusaku, Gotoh; Takayoshi, Kawahara; Yoshikazu, Sugimoto (Journal of Fertility Biomarkers, 2016)
Female fertility is an economically important trait in the dairy industry, and the fertility selection index has been developed as a method of including female fertility in the breeding goals of this industry. This index considers a combination of factors, including days open, number of inseminations per lactation, success after first insemination, and pregnancy within 70 d, 90 d, and 110 d after parity. Based on a genome-wide association study of the fertility selection index using 442 Holsteins, we found that the index is influenced by a variation in the thioredoxin fold region of the family with the sequence similarity 213, member A (FAM213A) protein. FAM213A is a CXXC motif-containing peroxiredoxin 2-like protein that regulates cellular redox status. A replacement of isoleucine with valine in FAM213A was associated with poor fertility in cows. The overexpression of FAM213AVal in bovine endometrial epithelial cells reduced reactive oxygen species to a lesser extent relative to the overexpression of FAM213AIle and caused a decrease in cyclooxygenase-2 expression. Downregulation of cyclooxygenase-2 led to a decline in prostaglandin E2, which is critical for implantation because it protects the conceptus from the maternal immune system. Cows with FAM213AVal showed lower levels of prostaglandin E2 than did cows with FAM213AIle, suggesting that cows with FAM213AVal are less fertile than cows with FAM213AIle because of their reduced uterine environment. Thus, the present study found that FAM213A unexpectedly modulates female fertility in cattle.
Keywords: GWAS; Holsteins; Fertility Selection Index; FAM213A.